On the finite state automorphism group of a rooted tree - Lavrenyuk, Y. (Algebra and Discrete Mathematics, 2002)
The normalizer of the finite state automorphism group of a rooted homogeneous tree in the full automorphism group of this tree was investigated. General form of elements in the normalizer was obtained and countability of the normalizer was proved.